A robust algorithm for analysis of intercepted HF traffic under noisy environment. (2017) - Walia, Gurjit Singh; Arora, Salil; Kapoor, Rajiv; Verma, Neelam; Singh, Tarandeep
The aim of this paper is to introduce a novel algorithm for retrieval of information from noisy intercepted traffic. The design considerations for HF protocol along with its simulation are elaborated. The main contribution of our research work is proposal for novel method for recovery information from a partially decoded noisy bit stream for HF protocols. Statistical properties of language such as unigram, bigram, trigram frequency have been exploited for design of cost function. Also, histogram analysis along with mean and variance statistics of language are extracted and used for design of another cost function. In our proposed analysis algorithm these cost functions are used for automatic analysis of recorded baseband protocols. The algorithm for automatic estimation of non-standard parameters such as baud rate, data format is proposed. The results and analysis of proposed algorithms are discussed for simulated HF protocol recordings.